Perceptual discrepancies in the experience and reporting of violence against children are more pronounced among social workers compared to laypeople - Mats Dahl; Leonard Ngaosuvan; Jessika Granberg Flintberg; Johanna Silfversparre; Lotta Stille; Marta Lasota; Sverker Sikström (PLoS ONE, 2025)
When violence against a child is reported to authorities, it is crucial that its severity is communicated effectively and evaluated accurately by professionals. This study, conducted in two phases, investigated perceptual differences in calibration and accuracy regarding psychological and physical violence against children among parents, social workers, and laypeople. In Phase 1, parents who had witnessed violence against their children, committed by a current or former partner, provided first-person narratives describing these events and rated the severity of the violence. In Phase 2, social workers and a control group (laypeople) read these narratives and rated the severity of the violence. Previous research on intimate partner violence suggests that recipients often underestimate the severity of psychological violence and overestimate that of physical violence. We hypothesized that this pattern would also apply for the control group, whereas social workers, due to their professional experience, would show smaller discrepancies compared to the parents. The results partially supported our hypotheses. The control group overestimated the severity of physical violence but did not significantly underestimate that of psychological violence. Unexpectedly, social workers overestimated the severity of psychological violence, resulting in larger perceptual discrepancies than the control group, contrary to the hypothesis. They also overestimated the severity of physical violence, but their ratings did not differ significantly from the control group. These findings suggest that professional experience does not necessarily reduce perceptual biases in assessing violence severity and may, in some cases, amplify them. This study highlights the complexities professionals face in evaluating violence against children and the need for further research, particularly considering potential influences such as desensitization, cognitive biases, and cultural factors.